2010
DOI: 10.1007/s10682-010-9388-z
|View full text |Cite
|
Sign up to set email alerts
|

Reflectance spectra and mating patterns support intraspecific mimicry in the colour polymorphic damselfly Ischnura elegans

Abstract: International audienceCoexistence of female colour morphs in animal populations is often consideredthe result of sexual conflict, where polymorphic females benefit from reduced male sexualharassment. Mate-searching males easily detect suitable partners when only one type offemale is present, but become challenged when multiple female morphs coexist, whichmay result in frequency-dependent mate preferences. Intriguingly, in damselflies, onefemale morph often closely resembles the conspecific male in body colorat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 47 publications
2
30
0
Order By: Relevance
“…This is surprising since it can be expected that andromorphs experience lower harassment rates and associated costs due to their male-like appearance, especially in populations where they are the rare morph [29,30,68,69]. Previous work further indicated that female phenotypic appearance varies with the population morph frequency in this system [51].…”
Section: Discussionmentioning
confidence: 99%
“…This is surprising since it can be expected that andromorphs experience lower harassment rates and associated costs due to their male-like appearance, especially in populations where they are the rare morph [29,30,68,69]. Previous work further indicated that female phenotypic appearance varies with the population morph frequency in this system [51].…”
Section: Discussionmentioning
confidence: 99%
“…Mature females occur as one of three discrete morphs: one blue, male-like, androchrome morph and two green-brown gynochrome morphs, which are called infuscans and infuscans-obsoleta [33]. Although the colouration of androchrome females and conspecific males is virtually identical, they can be distinguished by visual examination of external genitalia and abdomen width [5]. The polymorphism is controlled by a single autosomal locus with three alleles under a simple dominance hierarchy: androchrome >  infuscans  >  infuscans-obsoleta [7].…”
Section: Methodsmentioning
confidence: 99%
“…In damselflies, female-limited colour polymorphisms are common. Generally, one female morph (androchrome) resembles conspecific males in body colouration [5] and behaviour [6], whereas the other female morph(s) (gynochrome) are unlike males (or androchromes) in these traits [7]. …”
Section: Introductionmentioning
confidence: 99%
“…The striking resemblance in multiple traits of andromorphs to conspecific males has therefore prompted repeated proposals that andromorphs may be functional male-mimics [23] (or at least 'distracters' [24]). Empirical evidence confirms that andromorphs benefit from resembling males by receiving fewer mating attempts by males, at least when they are rare [25][26][27][28]. Indeed, morph-specific harassment levels and associated fitness costs in terms of reduced fecundity have been shown to vary in a negative frequency-dependent manner [29,30].…”
Section: Introductionmentioning
confidence: 99%